International Journal of Geo-Engineering - Chang, Ilhan; Kim, Young Sang.; Lee, Jong-Sub.; Finno, Richard J.; Lee, Jong-Sub.; Bang, Sangchul; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
The goal of this interdisciplinary journal is to provide a forum to discuss the knowledge and experience of geo-engineering from fundamentals to cutting edge technologies.
Keywords: Geotechnical engineering; Civil engineering; Engineering geology; Geotechnical Engineering and Applied Earth Sciences; Civil Engineering; Geoengineering